2015
DOI: 10.1186/s12909-015-0310-9
|View full text |Cite
|
Sign up to set email alerts
|

Training hospital managers for strategic planning and management: a prospective study

Abstract: BackgroundTraining is the systematic acquisition of skills, rules, concepts, or attitudes and is one of the most important components in any organization’s strategy. There is increasing demand for formal and informal training programs especially for physicians in leadership positions. This study determined the learning outcomes after a specific training program for hospital management teams.MethodsThe study was conducted during 2006 and 2007 at the Centre School of Public Health and Management, Faculty of Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 35 publications
2
42
0
3
Order By: Relevance
“…Another study carried out in Belgrade in 2007, showed that teaching strategic planning to hospital managers has a considerable impact on their ability to fulfill the mission, goals and vision of the hospital, [5] and the present study showed a significant difference between the mean awareness and attitude scores of individuals who had passed in-service training in strategic planning and those who had not.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Another study carried out in Belgrade in 2007, showed that teaching strategic planning to hospital managers has a considerable impact on their ability to fulfill the mission, goals and vision of the hospital, [5] and the present study showed a significant difference between the mean awareness and attitude scores of individuals who had passed in-service training in strategic planning and those who had not.…”
Section: Discussionsupporting
confidence: 60%
“…The increasing development of private and public hospitals and the improvement in their services and the ever-increasing advances in medical technology have put hospitals in a special competitive environment [1]. In this regard, managers and leaders in hospitals should deal with these changes by being farsighted, anticipating and analyzing environment changes, being flexible in making decisions about environment changes, and formulating the appropriate path to achieve the goals of the organization [2,3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amini et al conclude that the state of the systemic thinking factor among the majority of managers in the Medical University of Tehran is at a desired level and these managers abide by systemic thinking [32]. Terzic-Supic realized that teaching strategic planning and management plays an effective role in the optimal decision making of hospital managers [33]. and outside the organization [34].…”
Section: Discussionmentioning
confidence: 99%
“…É o que demonstra um estudo realizado em cento e sete hospitais públicos sérvios ligados a universidades públicas, que concluiu que, após um ano de capacitação dos líderes e administradores, o desempenho em relação à análise do ambiente externo e à administração de recursos financeiros apontou uma melhora significativa. A preocupação em fornecer qualidade na assistência foi um ponto frisado pela maioria dos hospitais, principalmente daqueles que reelaboraram sua missão e visão (Terzic-Supic et al, 2015). No foco de redução de custos na gestão hospitalar foi incluída a qualidade dos serviços ofertados à população (Vagnoni & Oppi, 2015).…”
Section: Revista De Gestão Em Sistemas De Saúde -Rgssunclassified